The physiology of cross-country skiing; a metabolic and cardiopulmonary update - Saltin, B. (4th International Congress on Science and Skiing, 2007)
In the first science Conference on skiing here in St Christoph a four-decade perspective was presented on the physiology of cc skiing. The major development in that time period was the enlarged reliance of the upper body in cc skiing; not only in the free style (skating), but in the classical (diagonal) technique as well. This has led to a series of investigations of the upper body in cc skiing, using invasive techniques both to study the metabolic and the cardiorespiratory responses.